Fanfiction: a influência das experiências multimodais nas práticas de leitura e escrita de adolescentes - Fernanda Tavares Paiva (2022)
New language uses emerged and became popular with the sociocultural transformations arising from globalization and technological evolution. In this context, digital literacy comes to light due to the demand for a conscious virtual positioning, as well as the proper use of the digital resources that are necessary to establish communication in contemporary times. Faced with this, digital genres appear in order to explore, recreate and expand a certain universe through fictional stories, like fanfictions, which are produced by fans. The general objective of this research is to analyze the impacts of multimodal experiences provided by fanfictions on the reading and writing practices of teenagers regularly enrolled in Elementary and High School. For this, i) the most frequent combinations of multimodal resources in fanfictions by teenage authors are identified; ii) we investigate the experiences of young authors in relation to the impacts of multimodal experiences on their writing and reading habits in the school environment and iii) the consequences of multimodal experiences on the agency of teenage readers and fanfiction authors are verified. This interpretative qualitative research followed the following steps: i) select young people, between 13 and 17 years old, who answer questions about the habit of reading and writing fanfictions, considering the resources in this genre; ii) organize the answers according to the recurrence of the narratives; iii) analyze the relevance of multimodality in these texts, the impact of multimodal experiences provided by fanfictions on the reading habit and writing and the importance of fanfictions in the reader/writer's identity process. The analysis points to the fact that multimodal experiences are part of the stimuli offered by fanfictions, as they directly involve the reader in the story. Furthermore, there was a recurrence of narratives that compare the digital genre with the identity of those who consume or produce it, since it presents separate materials that connect both.